Human endogenous retrovirus-H insertion screening - GULIYEV, MEHRAB; YILMAZ, SIBEL; SAHIN, KANIYE; MARAKLI, SEVGI; GOZUKIRMIZI, NERMIN (Molecular medicine reports, 2013)
Endogenous retroviruses (ERVs) and ERV-like sequences comprise 8% of the human genome. We aimed to analyze genome integration polymorphisms of human endogenous retrovirus (HERV)-H by the inter-retrotransposon amplified polymorphism (IRAP) technique using the sequences of LTR7A (450 bp), LTR7B (445 bp) and LTR7C (471 bp). Blood samples from 20 individuals (10 females and 10 males) of diverse ethnic origins were used for the determination of integration variations at the genomic level. Isolated genomic DNA was screened using 3 pairs of primers corresponding to LTR regions of the HERV-H gene. We observed insertion polymorphism patterns between 0-87% in all subjects. The findings obtained contribute to our understanding of the effects of HERV-H on variations within the human genome.